2001
DOI: 10.1080/j003v13n02_03
|View full text |Cite
|
Sign up to set email alerts
|

Service Dogs: A Compensatory Resource to Improve Function

Abstract: Objective. This study examined the physical, emotional, social, and economic functions of service dogs, the training methods for service dog/owner teams, and problems encountered with service dogs in relationship to occupational therapy literature and domain of concern. Method. A 31-question survey was developed based on the literature and Uniform Terminology (AOTA, 1994) and was completed by 202 service dog owners from 40 states and Canada. Results. Owners reported that service dogs assisted them in 28 functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
68
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 11 publications
(6 reference statements)
8
68
1
Order By: Relevance
“…This increased independence could bring substantial economic savings to health and care services; enabling individuals to complete tasks without assistance may also reduce the strain on often over-stretched community based support services [32] and increase the potential for individuals to contribute to the economy. Furthermore, by improving an individual’s capacity to actively engage in the community may not only bring direct benefits to society (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This increased independence could bring substantial economic savings to health and care services; enabling individuals to complete tasks without assistance may also reduce the strain on often over-stretched community based support services [32] and increase the potential for individuals to contribute to the economy. Furthermore, by improving an individual’s capacity to actively engage in the community may not only bring direct benefits to society (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For people with physical illness, disability research has suggested that contact with an animal leads to increased verbal interactions (Fick, 1993;Raina, Waltner-Toews, Bonnet, Woodward, & Abernathy, 1999;Roenke & Mulligan, 1998), greater community participation (Fairman & Huebner, 2000;Guest, Collis, & McNicholas, 2006;Valentine, Kiddoo, & LaFleur, 1993), increased social interactions and number of friends (Camp, 2001;Lane, McNicholas, & Collis, 1998) and community integration (Allen & Blascovich, 1996). For persons with mental illness in sheltered settings, pets were linked to improved social functioning (Barak, Savorai, Mavashev, & Beni, 2001;Haughie, Milne, & Elliot, 1992;Kovács, Kis, Rózsa, & Rózsa, 2004;Marr et al, 2000;Nathans-Barel, Feldman, Berger, Modai, & Silver, 2005).…”
Section: Pet Ownership and Community Integrationmentioning
confidence: 96%
“…Research has supported the ability of pets to get people out of the house, and into the broader community, for persons living with HIV=AIDS and physical disabilities (Allen, Hammon-Kellegrew, & Jaffe, 2000;Allen & Blascovich, 1996;Camp, 2001;Fairman & Huebner, 2000;Sachs-Ericsson, Hansen, & Fitzgerald, 2002).…”
Section: Pet Ownership and Community Integrationmentioning
confidence: 99%
“…Studies conducted by Camp [7] and Fairman and Huebner [13] provided preliminary research supporting the idea that service dogs can assist with performance of occupations. However, Camp indicated that there was a need for further research regarding how assistance dogs compare to an individual’s prior form or forms of AT.…”
Section: Introductionmentioning
confidence: 98%
“…The researchers concluded that they “…hope that this research will encourage more therapists to acknowledge service dogs as a new assistive technology, and to consider the recommendation of service dogs, under the right circumstances, for the people with physical disabilities they work with” (p. 113). It is clear that service dogs can assist persons with mobility impairments to engage more fully in valued daily occupations [8,9,10,11,12,13]. …”
Section: Introductionmentioning
confidence: 99%